Missed Diagnosis of Gestational Diabetes Mellitus Due to Selective Screening: Evidence from a Cross-Sectional Study in the West Nile Sub-Region, Uganda - Abindu, Vincent; Hope, Derick; Aleni, Mary; Andru, Monicah; Ayiasi, Richard Mangwi; Afayo, Victor; Oyet, Caesar; Kiconco, Ritah (Diabetes, Metabolic Syndrome and Obesity, 2024)
Purpose: To ascertain the prevalence and risk factors of gestational diabetes mellitus (GDM) in pregnant women receiving antenatal care (ANC) services within the West Nile subregion of Uganda. Patients and Methods: An analytical cross-sectional study was conducted on 233 pregnant women who are within 24–28 weeks of gestation and are receiving ANC services in selected hospitals. GDM was diagnosed according to the World Health Organization (WHO) criteria (2013). A questionnaire and anthropometric measurements were used to obtain relevant data. The chi-square test and logistic regression were used to determine the association between GDM and the study variables, including participants’ sociodemographic and medical characteristics. Results: The prevalence of hyperglycemia first detected in pregnancy among the participants tested was 8%. Overall, 7.45% had GDM and 0.53% had diabetes mellitus in pregnancy. The fasting plasma glucose test alone was positive in 86.7% of the GDM cases. The factors that were significantly associated with GDM included age ≥25 years (p = 0.017, AOR = 3.51) and body mass index (BMI) ≥25 kg/m2 (p = 0.024, AOR = 2.67). Out of the participants diagnosed with GDM, 28.6% did not have a known risk factor. Of the pregnant women with GDM, 57% would have been missed if the selective screening in the national clinical guidelines had been followed. Urinary tract infection (UTI) and Candida were detected in 36.36% and 13.85% of the participants, respectively. Conclusion: The study provides new data on the prevalence of GDM in rural settings in the West Nile subregion of Uganda. Of the participants, 7.5% were diagnosed with GDM, of which 57% would have been missed based on the selective screening of the national clinical guidelines. The study findings support the universal screening of GDM in pregnant women.
Keywords: Prevalence; Gestational diabetes mellitus; Risk factors; Selective screening